Guideline-Based Chinese Herbal Medicine Treatment Plus Standard Care for Severe Coronavirus Disease 2019 (G-CHAMPS): Evidence From China - Ye, Yong-an; , The G-CHAMPS Collaborative Group (Frontiers in Medicine, 2020)
Background In January, national guidelines were developed and recommended for use throughout China to fight coronavirus disease 2019 (COVID-19). Chinese herbal medicine (CHM) was also included as part of the treatment plans at various stages of COVID-19. Methods We conducted a pilot, randomized, controlled trial in patients with severe COVID-19 in Wuhan, China. Eligible adult patients were randomly assigned in a 2:1 ratio to receive either CHM plus standard care or standard care alone for 7 days. Results Between Jan 31, 2020, and Feb 19, 2020, 42 out of 100 screened patients were included in the trial: 28 in the CHM plus standard care group and 14 in the standard care alone group. Among 42 participants who were randomized (mean [SD] age 60.43 years [12.69 years]; 21 [21/42, 50%] were aged ≥ 65 years; and 35 [35/42, 83%] women, 42 (42/42, 100%) had data available for the primary outcome. For the primary outcome, one patient from each group died during treatment; the odds of a shift towards death was lower in the CHM plus group than the standard care alone group (common OR 0.59, 95% CI 0.148–2.352 P=0.454). Three (2 from the CHM plus group and 1 from the standard care alone group) patients progressed from severe to critical illness. Conclusions For the first time, the G-CHAMPS trial provided valuable information for the national guideline-based CHM treatment for hospitalized patients with severe COVID-19. CHM effects in COVID-19 may be clinically important and warrant further consideration and studies.